Design e transformação digital: uma abordagem orientada pelo design estratégico para a concepção de novos serviços no contexto farmacêutico - Klein, Aline Roque Borges (Universidade do Vale do Rio dos Sinos, 2019)
The present study sought to investigate the relationships between design, digital transformation and the challenges related to the construction of new services in the health context, focusing on pharmaceutical care services. To do so, we first sought to understand each of the related theoretical constructs, as well as their main concepts and their effects on society. This understanding supported the discussion of existing relationships in order to identify design contributions in the light of strategic design in this context. The knowledge generated from the literature review served as the basis for the planning and execution of an action research with a private pharmacy network, for the conception of new services that could increase the role of pharmacy in the health ecosystem, beyond its retail performance and connected with its digital transformation strategy. The results point out that designing services in digitally changing contexts requires designers to know how to analyze and interpret large volumes of data to design a set of varied and highly complex journeys in an omnichannel reality that integrates physical and digital environments. Overcoming this difficulty, a strategic design-driven service design process demonstrated great value from a metadesign perspective, contributing to the evolution of existing models to adapt to process design in omnichannel contexts.
Keywords: Transformação Digital; Design Estratégico; Design de Serviços; Omnichannel; Atenção Farmacêutica; Digital Transformation; Strategic Design; Service Design; Omnichannel; Pharmaceutical Care; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial